Is liver transplantation associated with decreased bone mass in climacteric women? O transplante hepático está associado a menor massa óssea em mulheres climatéricas? - Luiz Francisco Baccaro; Ilka de Fátima Boin; Lúcia Costa-Paiva; Aline Garcia Leal; Celso Dario Ramos; Aarão Mendes Pinto-Neto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2012)
PURPOSE: To evaluate whether climacteric women undergoing liver transplantation had higher prevalence of decreased bone mass than those without any liver disease. METHODS: A cross-sectional study with 48 women receiving follow-up care at a university hospital in Southeastern Brazil, from February 4th 2009 to January 5th 2011, was conducted. Of these women, 24 were 35 years or older and had undergone liver transplantation at least one year before study entry. The remaining 24 women had no liver disease and their ages and menstrual patterns were similar to those of transplanted patients. Laboratorial tests (follicle-stimulating hormone and estradiol) and bone density measurements of the lumbar spine and femur (equipment Hologic, Discovery WI) were performed. Statistical analysis was carried out by Fisher's exact test, simple Odds Ratio (OR), and multiple logistic regression. RESULTS: Mean age of the women included in the study was 52.8 (±10.7) years-old, 27.1% were premenopausal and 72.9% were peri/postmenopausal. Approximately 14.6% of these women exhibited osteoporosis and 35.4% had low bone mass. The following items were associated with decreased bone mass: being postmenopausal (OR=71.4; 95%CI 3.8 - 1,339.7; p<0.0001), current age over 49 years-old (OR=11.4; 95%CI 2.9 - 44.0; p=0.0002), and serum estradiol levels lower than 44.5 pg/mL (OR=18.3; 95%CI 3.4 - 97.0; p<0.0001). Having a history of liver transplantation was not associated with decreased bone mass (OR=1.4; 95%CI 0.4 - 4.3; p=0.56). CONCLUSION: Liver transplantation was not associated with decreased bone mass in this group of climacteric women. OBJETIVO: Avaliar se mulheres climatéricas submetidas a transplante de fígado tiveram maior prevalência de massa óssea diminuída do que aquelas sem antecedente de doença hepática. MÉTODOS: Estudo de corte transversal, com 48 mulheres em acompanhamento ambulatorial em um hospital universitário na região Sudeste do Brasil, no período de 04 de fevereiro de 2009 a 05 de janeiro de 2011. Foram incluídas 24 mulheres submetidas a transplante hepático há pelo menos um ano, com idades igual ou superior a 35 anos, e 24 sem antecedente de doença hepática, com idade (± três anos) e padrão menstrual semelhante ao das transplantadas. As mulheres foram submetidas a exames laboratoriais (hormônio folículo estimulante e estradiol) e densitometria óssea de coluna lombar e fêmur, com equipamento Hologic, Discovery WI. A análise estatística foi realizada por meio do teste exato de Fisher, por Odds Ratio (OR) simples e pela regressão logística múltipla. RESULTADOS: A média etária das mulheres incluídas no estudo foi de 52,8 (±10,7) anos, sendo que 27,1% estavam na pré-menopausa e 72,9%, na peri/pós-menopausa. Aproximadamente 14,6% dessas mulheres apresentaram osteoporose e 35,4%, baixa massa óssea. Os seguintes itens foram associados com massa óssea diminuída: estar na pós-menopausa (OR=71,4; IC95% 3,8 - 1.339,7; p<0,0001), idade atual maior que 49 anos (OR=11,4; IC95% 2,9 - 44,0; p=0,0002) e nível de estradiol sérico menor que 44,5 pg/mL (OR=18,3; IC95% 3,4 - 97,0; p<0,0001). Ter antecedente de transplante hepático não se associou massa óssea diminuída (OR=1,4; IC95% 0,4 - 4,3; p=0,5). CONCLUSÃO: O transplante hepático não se associou massa óssea diminuída nesse grupo de mulheres climatéricas.